2017
DOI: 10.1186/s12974-017-0859-9
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to gestational diabetes mellitus induces neuroinflammation, derangement of hippocampal neurons, and cognitive changes in rat offspring

Abstract: BackgroundBirth cohort studies link gestational diabetes mellitus (GDM) with impaired cognitive performance in the offspring. However, the mechanisms involved are unknown. We tested the hypothesis that obesity-associated GDM induces chronic neuroinflammation and disturbs the development of neuronal circuitry resulting in impaired cognitive abilities in the offspring.MethodsIn rats, GDM was induced by feeding dams a diet high in sucrose and fatty acids. Brains of neonatal (E20) and young adult (15-week-old) off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
79
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 69 publications
4
79
2
1
Order By: Relevance
“…This programming effect of early‐life diet on microglia extends beyond the hypothalamus; microglia are also increased in density in the hippocampus in adults that have been overfed as neonates . Similarly, recent studies have shown a primed hippocampal microglial profile in adult offspring from high‐saturated‐fat diet‐fed dams . Performance in hippocampally‐mediated learning tasks is less efficient in these rats and it appears that microglia in neonatally overfed rats are less responsive to a learning task compared to those in control‐fed rats .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This programming effect of early‐life diet on microglia extends beyond the hypothalamus; microglia are also increased in density in the hippocampus in adults that have been overfed as neonates . Similarly, recent studies have shown a primed hippocampal microglial profile in adult offspring from high‐saturated‐fat diet‐fed dams . Performance in hippocampally‐mediated learning tasks is less efficient in these rats and it appears that microglia in neonatally overfed rats are less responsive to a learning task compared to those in control‐fed rats .…”
Section: Introductionmentioning
confidence: 95%
“…16 Similarly, recent studies have shown a primed hippocampal microglial profile in adult offspring from high-saturated-fat diet-fed dams. 4,17 Performance in hippocampally-mediated learning tasks is less efficient in these rats 4,17 and it appears that microglia in neonatally overfed rats are less responsive to a learning task compared to those in control-fed rats. 16 Microglia have region-specific heterogeneity with different responses to stimuli in different brain regions.…”
mentioning
confidence: 99%
“…During adolescence, the hippocampus reaches peak volume, and begins to undergo synaptic pruning, eliminating unused connections [60,61], and prior studies have shown that the CA3 hippocampal subfield gradually begins to decrease in volume during mid childhood [61,62]. Work by Vuong et al found that synaptic pruning is delayed in juvenile rats exposed in utero to obese mothers with GDM [63]. In their findings, inflammation and recruitment of microglial cells occurred during post-natal development in the hippocampus, along with a reduction in synaptic pruning, and the animals presented with altered hippocampal morphology.…”
Section: Discussionmentioning
confidence: 99%
“…In their findings, inflammation and recruitment of microglial cells occurred during post-natal development in the hippocampus, along with a reduction in synaptic pruning, and the animals presented with altered hippocampal morphology. These findings suggest that prenatal environmental insults can result in hippocampal inflammation, reductions in synaptic pruning and altered hippocampal development [63]. Interestingly, Hershey et al, found that children with Type 1 diabetes had increased hippocampal volume, despite the commonly reported decreased volume in adults with Type 1 and Type 2 diabetes [64].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental investigations in animals indicated that uncontrolled diabetes mellitus was associated with morphological and functional alterations in the brain [12][13][14]. Hippocampus, a structure critical to cognitive processes, has been shown to undergo apoptotic cell death when subjected to hyperglycemic insult [15][16][17].…”
Section: Introductionmentioning
confidence: 99%